Jews in the Americas, 1776-1826
1 online resource (l, 468 pages)
Keywords: "The period between 1776-1826 signalled a major change in how Jewish identity was understood both by Jews and non-Jews throughout the Americas. Jews in the Americas, 1776-1826 brings this world of change to life by uniting important out-of-print primary sources on early American Jewish life with rare archival materials that can currently be found only in special collections in Europe, England, the United States, and the Caribbean"--